Cross-country skiing movement factorization to explore relationships between skiing economy and athletes' skills - Pellegrini, B.; Zoppirolli, C.; Boccia, G.; Bortolan, L.; Schena, F. (Scandinavian Journal of Medicine & Science in Sports, 2018)
We investigated the relationships between the biomechanics of the double poling (DP) technique in cross-country skiing, its economy and athletes` skill. To this aim, skiers` motion has been factorized into components through principal component analysis (PCA).Eight high-level (HL) and eight regional level (RL) male cross-country skiers performed a 5-min submaximal DP trial while roller skiing on a treadmill at 14 km h-1 and 2° incline. Whole-body kinematics was recorded with a motion capture system. PCA was applied to markers coordinates to extract principal movements (PMk), which were ranked by their variance. Energy cost of locomotion (EC) was calculated from ergospirometric measurements.